Outcomes of Patients With Sepsis and Septic Shock Requiring Source Control: A Prospective Observational Single-Center Study. (1st December 2022) - Naqvi, Fatima; Jain, Pranav; Umer, Amna; Rana, Bilal; Hadique, Sarah
Abstract : OBJECTIVES: Source control is important in management of septic shock. We studied differences in outcomes of patients with sepsis and septic shock who required source control intervention compared with those who did not need such intervention and the effect of the timing of source control on various clinical outcomes. DESIGN: Prospective observational study from February 28, 2020, to March 31, 2021. SETTING: Medical ICU of academic quaternary medical center. PATIENTS: Two hundred five adult (≥18 yr) ICU patients. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Patients were divided into a medical treatment group and a source control group. Patients requiring source control were further divided into early (intervention performed < 24 hr) and late (≥ 24 hr) source control groups. The primary outcomes were 30-day and ICU mortality. Secondary outcomes were ICU and hospital length of stay (LOS), days on mechanical ventilation, and need for renal replacement therapy. A total of 45.9% patients underwent source control. Of these, early source control was performed in 44.7% and late source control in 55.3% of patients. There was no significant difference in 30-day mortality or ICU mortality in the medical versus source control groups or in early versus late source control groups. Compared with the medical group, mean hospital LOS (11.5 vs 17.4 d; p < 0.01) and ICU LOS (5.2 vs 7.7 d; p < 0.01) were longer in the source control group. The hospital LOS (12.5 vs 21.4 d; p < 0.01) and ICU LOS (5.2 vs 9.7 d; p < 0.01) were also longer in patients who had delayed source control than in patients who had early source control. There were no significant differences in other outcomes. CONCLUSIONS: Although mortality was similar, patients who had delayed source control had a longer ICU and hospital LOS. Early source control may improve health care utilization in septic shock patients.